Viscosity and Interfacial Tension of Binary Mixtures Consisting of an n-Alkane, Branched Alkane, Primary Alcohol, or Branched Alcohol and a Dissolved Gas Using Equilibrium Molecular Dynamics Simulations - Hewa Kankanamge, Chathura Jayan Kankanamge; Lenahan, Frances; Klein, Tobias; Fröba, Andreas Paul (International Journal of Thermophysics, 2022)
This study aims to characterize binary mixtures consisting of a liquid with a dissolved gas by determining their dynamic viscosity and interfacial tension using equilibrium molecular dynamics (EMD) simulations in the temperature range between (298 and 573) K and for solute mole fractions up to 0.20. With the help of a systematic variation of solvent and solute molecules, the influence of their molecular characteristics, e.g., in form of size, shape, or polarity, on the thermophysical properties of the mixtures is discussed. For this, eight different alkanes and alcohols with a carbon number between 12 and 40 as solvents and seven solutes in form of hydrogen, helium, methane, water, nitrogen, carbon monoxide, or carbon dioxide are studied. Using EMD simulations, the liquid dynamic viscosity is determined in the slightly compressed liquid phase close to saturation conditions. Simulations at vapor-liquid-equilibrium (VLE) are performed to determine the interfacial tension and to calculate the solute molecules at the vapor-liquid interface. To check the applicability of the EMD simulations, data for the dynamic viscosity and interfacial tension from this work are compared to experimental data of binary mixtures with the same solutes and similar solvents. The results from this work show that the impact of the dissolved gas on the thermophysical properties is strongly depending on its molecular characteristics. For example, the properties of mixtures containing dissolved He are usually within combined uncertainties with the ones of the pure solvent. In contrast, dissolving CO2 leads to a pronounced reduction in both properties at comparable solute mole fractions. For the molecular characteristics of the solvent, the carbon chain length is shown to influence mainly the interfacial tension and the polarity mainly influences the viscosity.
Keywords: Binary mixtures; Gases; Hydrocarbons; Interfacial tension; Molecular dynamics simulations; Viscosity